Menu Close

let-f-x-x-1-n-arctan-nx-calculate-f-n-0-




Question Number 62210 by maxmathsup by imad last updated on 17/Jun/19
let f(x) =(x+1)^n  arctan(nx)  calculate f^((n)) (0).
letf(x)=(x+1)narctan(nx)calculatef(n)(0).
Commented by mathmax by abdo last updated on 24/Jun/19
let determine f^((p)) (x)  leibniz formulse give  f^((p)) (x) =Σ_(k=0) ^p  C_p ^k    {(x+1)^n }^((k))   (arctan(nx))^((p−k))     we have   (X^n )^((k))  =0 si k>n  (X^n )^((1))  =nX^(n−1)  ⇒(X^n )^((k))  =n(n−1)..(n−k+1)X^(n−k) =((n!)/((n−k)!))X^(n−k)   if k≤n  and   (X^n )^((n))  =n!   so for p≥n we get  f^((p)) (x) =Σ_(k=0) ^n  C_p ^k   {(x+1)^n }^((k))  {arctan(nx)}^((p−k))  +Σ_(k=n+1) ^p  C_p ^k  {(x+1)^n }^((k)) {arctan(nx)}^((p−k))   =Σ_(k=0) ^n   C_p ^k    ((n!)/((n−k)!))(x+1)^(n−k)   {arctan(nx)}^((p−k))   ⇒  f^((n)) (x) =Σ_(k=0) ^n  C_n ^k   ((n!)/((n−k)!)){ arctan(nx)}^((n−k))   =Σ_(k=0) ^n  C_n ^k   k!  ((n!)/(k!(n−k)!)) {arctan(nx)}^((n−k))  =Σ_(k=0) ^n   k!  (C_n ^k )^2  { arctan(nx)}^((n−k))   we have (arctan(nx))^((1))  =(n/(1+n^2  x^2 )) =(n/(n^2 (x^2 +(1/n^2 )))) =(1/(n(x−(i/n))(x+(i/n))))  =(1/(n(2(i/n)))){  (1/(x−(i/n))) −(1/(x+(i/n)))} =(1/(2i)){ (1/(x−(i/n))) −(1/((x+(i/n))))} ⇒  {arctan(nx)}^((p))  =(1/(2i)){  ((1/(x−(i/n))))^((p−1)) −((1/(x+(i/n))))^((p−1)) }  =(1/(2i)){ (((−1)^(p−1) (p−1)!)/((x−(i/n))^p )) −(((−1)^(p−1) (p−1)!)/((x+(i/n))^p ))} ⇒  {arctan(nx)}^((n−k))  =(1/(2i))(−1)^(n−k−1) (n−k−1)!{(1/((x−(i/n))^(n−k) )) −(1/((x+(i/n))^(n−k) ))} ⇒  f^((n)) (x) =(1/(2i))Σ_(k=0) ^n  k!(C_n ^k )^2  (−1)^(n−k−1) (n−k−1)!{(1/((x−(i/n))^(n−k) )) −(1/((x+(i/n))^(n−k) ))}
letdeterminef(p)(x)leibnizformulsegivef(p)(x)=k=0pCpk{(x+1)n}(k)(arctan(nx))(pk)wehave(Xn)(k)=0sik>n(Xn)(1)=nXn1(Xn)(k)=n(n1)..(nk+1)Xnk=n!(nk)!Xnkifknand(Xn)(n)=n!soforpnwegetf(p)(x)=k=0nCpk{(x+1)n}(k){arctan(nx)}(pk)+k=n+1pCpk{(x+1)n}(k){arctan(nx)}(pk)=k=0nCpkn!(nk)!(x+1)nk{arctan(nx)}(pk)f(n)(x)=k=0nCnkn!(nk)!{arctan(nx)}(nk)=k=0nCnkk!n!k!(nk)!{arctan(nx)}(nk)=k=0nk!(Cnk)2{arctan(nx)}(nk)wehave(arctan(nx))(1)=n1+n2x2=nn2(x2+1n2)=1n(xin)(x+in)=1n(2in){1xin1x+in}=12i{1xin1(x+in)}{arctan(nx)}(p)=12i{(1xin)(p1)(1x+in)(p1)}=12i{(1)p1(p1)!(xin)p(1)p1(p1)!(x+in)p}{arctan(nx)}(nk)=12i(1)nk1(nk1)!{1(xin)nk1(x+in)nk}f(n)(x)=12ik=0nk!(Cnk)2(1)nk1(nk1)!{1(xin)nk1(x+in)nk}
Commented by mathmax by abdo last updated on 24/Jun/19
f^((n)) (0) =(1/(2i))Σ_(k=0) ^n  k!(C_n ^k )^2  (−1)^(n−k−1) (n−k−1)!{(1/((−(i/n))^(n−k) ))−(1/(((i/n))^(n−k) ))} .
f(n)(0)=12ik=0nk!(Cnk)2(1)nk1(nk1)!{1(in)nk1(in)nk}.

Leave a Reply

Your email address will not be published. Required fields are marked *